(untitled) (ACME, 2020)
Focusing on Rutilius Namatianus’ farewell to Rome, described in the first section of the De reditu suo, this paper wants to offer an overall reading of the different details that characterize this scene. It aims to examine in particular the passages of the poem preceding and following the famous “hymn” dedicated by the author to the city (i, 47-164): the farewell representation is included between the beginning of the poem, where Rutilius explains the reasons why he is going back to Gaul (see mainly 19-34), and the section in which he portrays the view of Rome from a distance by combining perceptions with imagination (189-204). Moreover, through a comparison with some passages of the elegiac tradition, mainly Ovidian, this article studies the similarities between the poet and a lover forced to leave his beloved. This analogy, already known by scholars, has interesting relationships with some scenes described, among other works, in the Heroides. As a conclusion, the final goal of the paper is to show how Rutilius probably models his farewell on a particular framework, by suggesting images and themes typical of love poetry.